Electrosprayed nanoparticle delivery system for controlled release - Eltayeb, M; Stride, E; Edirisinghe, M; Harker, A (Elsevier, 2016)
This study utilises an electrohydrodynamic technique to prepare core-shell lipid nanoparticles with a tunable size and high active ingredient loading capacity, encapsulation efficiency and controlled release. Using stearic acid and ethylvanillin as model shell and active ingredients respectively, we identify the processing conditions and ratios of lipid:ethylvanillin required to form nanoparticles. Nanoparticles with a mean size ranging from 60 to 70 nm at the rate of 1.37 × 109 nanoparticles per minute were prepared with different lipid:ethylvanillin ratios. The polydispersity index was ≈ 21% and the encapsulation efficiency ≈ 70%. It was found that the rate of ethylvanillin release was a function of the nanoparticle size, and lipid:ethylvanillin ratio. The internal structure of the lipid nanoparticles was studied by transmission electron microscopy which confirmed that the ethylvanillin was encapsulated within a stearic acid shell. Fourier transform infrared spectroscopy analysis indicated that the ethylvanillin had not been affected. Extensive analysis of the release of ethylvanillin was performed using several existing models and a new diffusive release model incorporating a tanh function. The results were consistent with a core-shell structure.